PTH-156 The role of bronchoscopy and ebus in the modern multidisciplinary management of oesophageal and gastric cancer. (22nd June 2015) - Hey, SY; Chalmers, GW; Craig, C; MacKay, CK; Fullarton, GM; Forshaw, MJ
Abstract : Introduction: The optimal role of endobronchial ultrasound (EBUS) and bronchoscopy in the current TNM staging protocol for oesophago-gastric (OG) cancer remains undetermined. These procedures are often used following multidisciplinary team (MDT) discussion, to circumvent the technical limitation of the gold standard endoscopic ultrasound (EUS) in assessing indeterminate mediastinal nodes or the extent of tracheobronchial invasion identified on CT or PET scan. We aim to investigate the effectiveness of EBUS and bronchoscopy in our routine practice of clinical staging of OG cancers and its subsequent impact on outcome. Method: Retrospective, structured review of all MDT records between 1 January 2009 and 31 December 2013 was conducted from regional database. All patients who underwent either EBUS or bronchoscopy for staging of oesophageal or gastric cancers were included. The records of EBUS and bronchoscopy performed were retrospectively interrogated in the NHS Unisoft database, together with an analysis of the indication, findings in correlation with pre-procedural imaging, outcome and limitations. Results: Over the 7-year period, 15 patients (12M;3F) were identified, of whom 6 underwent EBUS and 9 had bronchoscopy. All 6 EBUS were indicated for primary N staging (5 oesophageal, 1 gastric) and had successful fine needle aspirations. Of these, 4 were performed directly following PET identification of avid mediastinal nodes while 2 had unsuccessful nodal biopsy from preceding EUS. Following EBUS, 4 patients had completed clinical staging whereas 2 had required further staging laparoscopy for distal and junctional oesophageal cancer, respectively. All 9 bronchoscopies were used to assess tracheobronchial invasion or concomitant suspicious lung lesion, of which 7 were primary staging (6 oesophageal, 1 gastric) and 2 were re-staging following neoadjuvant therapy (1 oesophageal, 1 gastric). Of these, only 1/9 had pre-procedure EUS. Tracheal invasion was excluded in 7, while 2 had synchronous lung and oesophageal malignancies diagnosed from cytology outcomes. Of the 15 cases, 7 were subsequently offered curative resection, while the remaining 8 had either radical or palliative chemo- or radiotherapy. No post-procedural complications were identified. Conclusion: Accurate clinical staging improves survival outcomes in OG cancer, by identifying patients potentially suitable for curative resection. Our series reveals EBUS and bronchoscopy as useful additions to conventional modalities in staging of OG cancer. With its good safety profile, it may be appropriate to consider early referral for EBUS or bronchoscopy, particularly in the radiological presence of indeterminate tracheobronchial invasion or mediastinal node involvement. Disclosure of interest: None Declared.